KEY AUDIT MATTERS IN PRACTICE: AN EMPIRICAL STUDY OF AUDITOR REPORTING IN INDONESIA - Angelita Angelita; Randy Kuswanto (Kajian Akuntansi, 2025)
This study aims to explore and analyze the practice of KAM disclosure by auditors in Indonesia and identify whether there are certain patterns or trends in KAM disclosure based on the characteristics of the company, auditor, or industry concerned. This study uses descriptive analysis method with a total sample of 1,664 observations. The main source of information of this study is secondary data obtained from audit reports that have been published by IDX listed companies in 2022 and 2023. The test results prove: First, the main topics of auditor concern remain consistent, namely revenue recognition, receivables, and fixed assets. Second, there is an increase in standardization towards more transparent audit reporting. Third, there is an observable pattern in the distribution of auditor. This research data still does not explore more deeply how auditors disclose KAM, so further research is needed. Efforts that can be made include in-depth interviews with auditors at various KAPs, analyzing KAM disclosure based on KAP size, or assessing more deeply the effectiveness of KAM disclosure policies and their impact on overall audit quality.